Analisis Kebiasaan Mengkonsumsi Mie Instan Pada Mahasiswa Di UD. Diana Kelurahan Batunadua Jae - Nasution, Nurul Hidayah; Jufri, Soleman; Saindah, Sopia Nur; Hastuty, Renni; Hasian, Putri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Instant noodles are block-shaped noodle products that are ready to be cooked and are usually in a dry condition accompanied by spices and/or seasoning oil which are packaged in separate packages. The results of the 2018 Basic Health Research stated that 7.8% of Indonesians consume instant noodles/other foods every day, 58.8% of Indonesians consume 1 to 6 packs per week and 33.8% consume instant noodles for less than three months. The reason instant noodles are a favorite food among all people is due to the lack of time in serving daily food. The aim of the study was to find out how the habit of consuming instant noodles for the health of boarding children at UD. Diana, Village of Batunadua Jae. This type of qualitative research, phenomenological study design. The informants of this study were boarding children at UD. Diana Batunadua sub-district as many as 10 informants. The informant selection technique was purposive sampling. Data collection technique is interview using an interview guide. Data processing includes data reduction and display. Data analysis consists of specifying certain symbols in making predictions on data, drawing conclusions and verifying and narrating the results. The results showed that informants like to consume instant noodles on the grounds that instant noodles are easier, more practical, delicious, easy to reach and relatively cheap. Most of the informants consumed instant noodles 1-2 times a week. Most of the informants felt no complaints and a small number of informants felt complaints such as itching around the body, nausea, difficulty defecating and headaches. Most of the informants really like to consume instant noodles even though they already know the impact on health. It is suggested that informants can sort out healthy foods to avoid various health impacts.